2014
DOI: 10.6061/clinics/2014(04)09
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzymes serum levels in patients with chronic kidney disease on hemodialysis: a comprehensive review

Abstract: We reviewed the literature regarding the serum levels of the enzymes aspartate aminotransferase, alanine aminotransferase, and gamma-glutamyl transferase in patients with chronic kidney disease on hemodialysis with and without viral hepatitis.Original articles published up to January 2013 on adult patients with chronic kidney disease on hemodialysis were selected. These articles contained the words “transaminases” “aspartate aminotransferase” “alanine aminotransferase” “gamma glutamyl transferase,” “liver enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 63 publications
7
54
2
1
Order By: Relevance
“…This finding is consistent with a previous study that reported lower SGPT levels in patients with CKD on hemodialysis (with or without viral hepatitis) than in patients with normal renal function. 37 This may explain the lack of an association between SGPT and CKD in the present study.…”
Section: Discussionmentioning
confidence: 56%
“…This finding is consistent with a previous study that reported lower SGPT levels in patients with CKD on hemodialysis (with or without viral hepatitis) than in patients with normal renal function. 37 This may explain the lack of an association between SGPT and CKD in the present study.…”
Section: Discussionmentioning
confidence: 56%
“…There was in one study an increase in the sensitivity of ALT from 55% to 76% for the diagnosis of discrete liver diseases and specificity was reduced from 97% to 89% when the ULN was reduced [11,12]. A second study found the risk of mortality from liver disease was higher in individuals with normal levels of ALT that were close to the ULN compared with individuals with lower ALT levels in a large Korean population.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a proposal to reduce the upper limit of the normal (ULN) of ALT to approximately 70% of the conventional limits while screening for liver abnormalities in patients without CKD [11]. There was in one study an increase in the sensitivity of ALT from 55% to 76% for the diagnosis of discrete liver diseases and specificity was reduced from 97% to 89% when the ULN was reduced [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with ESRD often have lower baseline aminotransferases for unclear reasons (possibly caused by hemodilution, pyridoxine deficiency, or homocysteine elevation). 11 In these patients, aminotransferase levels that are within the normal range may mask increased inflammatory activity. When aminotransferases are noted to increase from baseline, even if still within the normal range, liver biopsy may be needed to more accurately demonstrate the burden of inflammation.…”
Section: Introductionmentioning
confidence: 99%